Editorial: Rural Schools as Hubs for Socio-educational Development of Communities - Henderson, Robyn; Lúcio, Joana (Australian and International Journal of Rural Education, 2017)
This special issue of the Australian and International Journal of Rural Education presents 10 papers on the theme of rural schools as hubs for the socio-educational development of communities. The idea for a collection of papers on this theme originated in a large, multi-paper symposium presented at the European Conference on Educational Research in August 2016 in Dublin, Ireland.